ANALISIS PENDAPATAN KELUARGA PETANI SAGU DI DESA ALINDAU KECAMATAN SINDUE KABUPATEN DONGGALA - Dafina Howara; Sulmi Sulmi; Amalia Noviyanty (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
Sago is a source of staple food for the people in the eastern part of Indonesia as it contains high carbohydrate.  Many types of traditional foods use sago as their raw material.This leads to sago being utilized as alternative food besides rice, corn and tubers to support the national food security. The utilization of sago for making traditional foods can potentially increase income of the people in general.  Advance in food technology has allowed the creation of delicious and nutritious food from sago processing.  The purpose of this study were to (1) determine the income derived from the business of traditional food made from sago, and (2) analyze the revenue contribution generated from the traditional food made from sago on household income of sago farmers.  Samples were selected purposively with the number of respondents was 10 sago farmers in Alindau village.  Data collected was through observations and interviews using questionnaires.  Quantitative descriptive techniques such as income and contribution analysis were used to analyze the data.  Alindau village is one of the villages in Donggala which still has sago palm plants.  The processing of sago starch is still done traditionally using a grated coconut.  The sago farm in Alindau village has not yet currently become the main source of income for the farmer families due to increasing illegal pruning of the plant leaves which then used for forage or sold leading to badly plant growth. The income generated from the sago farming was IDR 865,000.00 in average. However, as sago is only sold in the form of flour and no further processing has been done yet, there is no contribution coming from revenue generated from the processed sago, thus, the second purpose of this study was not achieved.Keywords: Income, Sago and Traditional Food.